2022
DOI: 10.3390/cancers14246094
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for the Detection and Risk Stratification of Aggressive Prostate Cancer

Abstract: Current strategies for the clinical management of prostate cancer are inadequate for a precise risk stratification between indolent and aggressive tumors. Recently developed tissue-based molecular biomarkers have refined the risk assessment of the disease. The characterization of tissue biopsy components and subsequent identification of relevant tissue-based molecular alterations have the potential to improve the clinical decision making and patient outcomes. However, tissue biopsies are invasive and spatially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 225 publications
0
3
0
Order By: Relevance
“…A combination of GSTP1, RASSF1, and APC analysis showed better performance than histological evaluation of biopsy samples, identifying PC in 62% and 68% of histologically negative biopsies in two separate large studies (analyzing 498 and 350 biopsies, respectively) [47,49]. Therefore, 5-mC biomarkers may potentially overcome the limitations of biopsy sampling and aid in the detection of PC in histologically occult biopsy cores [53]. In addition, studies have suggested that the Prostate Cancer Antigen 3 (PCA3) score and the Prostate Health Index (PHI) could improve the accuracy of predicting the presence of PC at repeat biopsy [54].…”
Section: Discussionmentioning
confidence: 99%
“…A combination of GSTP1, RASSF1, and APC analysis showed better performance than histological evaluation of biopsy samples, identifying PC in 62% and 68% of histologically negative biopsies in two separate large studies (analyzing 498 and 350 biopsies, respectively) [47,49]. Therefore, 5-mC biomarkers may potentially overcome the limitations of biopsy sampling and aid in the detection of PC in histologically occult biopsy cores [53]. In addition, studies have suggested that the Prostate Cancer Antigen 3 (PCA3) score and the Prostate Health Index (PHI) could improve the accuracy of predicting the presence of PC at repeat biopsy [54].…”
Section: Discussionmentioning
confidence: 99%
“…For malignant mesothelioma, this term is frequently preferred to "invasive", which defines cancers that "spread beyond the layer of tissue in which it developed", especially for cases associated with the poorest clinical outcomes [1]. For aggressive tumors, investigations of their molecular alterations are useful tools that may improve clinical decisions and patient outcomes [2]. Previous studies have shown the usefulness of proteome studies as considerable discordance can be found between genomic mutations and protein expression levels, due to post-transcriptional regulation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although cancer development is characterized by multiple genetic and epigenetic alterations as well as aberrant gene expression, the exact molecular events that contribute to cancer progression, including PCa, are still not fully explored. The combined assessment of certain clinically established criteria, such as PSA and the Gleason score, alongside molecular markers, including driver mutations and gene expression signatures, has been highlighted as putative biomarkers for PCa risk stratification and prognosis [8].…”
Section: Introductionmentioning
confidence: 99%